The effect of Traumeel LT ad us. vet. on the perioperative inflammatory response after castration of stallions: a prospective, randomized, double-blinded study - Laves, Julia; Wergin, Melanie; Bauer, Natali; Müller, Simon Franz; Failing, Klaus; Büttner, Kathrin; Hagen, Alina; Melzer, Michaela; Röcken, Michael (Frontiers in Veterinary Science, 2024)
IntroductionStallion castration is a standard procedure with a risk of post-surgical complications. Castration induces an acute phase response (APR). Serum Amyloid-A (SAA) is a well-studied major acute phase protein (APP), that has been shown to be a good marker for the development of post-surgical complications. The current gold standard for reducing the APR after castration is Flunixin-Meglumin, which is a non-steroidal anti-inflammatory drug (NSAID) inhibiting COX1/2. In contrast, Traumeel LT ad us. vet. can modulate the APR by induction of the inflammation resolution. The aim of this study was to compare the effect of Flunixin-Meglumin and Traumeel LT ad us. vet. on the acute phase response.Material and methodsA total of 60 stallions were recruited and 54 stallions entered the study with 27 stallions in each treatment group. The stallions were treated pre- and postoperatively with either Flunixin-Meglumin (FL) or with Traumeel LT ad us. vet. (TR). Blood was taken before and 24 h, 48 h and 72 h after castration. The following main parameters were assessed: SAA, fibrinogen, iron, white blood cells, neutrophils, Interleukin1ß, and cortisol. Wound healing and pain were assessed at 8 time points.ResultsThe main variable SAA was increased after surgery reaching a mean value of 122 µg/ml in the FL group and a mean SAA of 226 µg/ml in the TR group 48 h after surgery, reaching a significant difference only at the 24 h timepoint (p = 0.03). All stallions had the highest pain summary score 8 hours after surgery, with decreasing values thereafter. The pain scores were not statistically different at any time point. In the FL group five stallions developed a suture dehiscence compared to only one stallion in the TR group (p = 0.001).DiscussionWithin the limitations of this study, Traumeel LT ad us. vet. seems to have proresolving effects on the inflammation induced by surgery making it a valuable treatment to reduce the APR induced by castration. Due to its different mode of action, Traumeel LT ad us. vet. might be an alternative treatment option if gastrointestinal side effects or renal side effects of NSAIDs should be avoided. Further studies are needed combining Traumeel LT ad us. vet. and Flunixin.